A new honeycomb MOF for C2H4 purification and C3H6 enrichment by separating methanol to olefin products. Issue 5 (18th January 2023) - Zhang, Lin; Ma, Li-Na; Wang, Gang-Ding; Hou, Lei; Zhu, Zhonghua; Wang, Yao-Yu
Abstract : A new C3 H6 -selective MOF based on infinite helix SBUs was constructed, realizing the effective separation of C2 H4 –C3 H6 to not only yield ≥99.9% purity of C2 H4 by a one-step method but also greatly increase the purity of C3 H6 in the adsorbed mixtures. Abstract : C2 H4 and C3 H6 are the main products of the MTO (methanol to olefins) process and they are also important industrial raw materials. However, it is a great challenge to separate them from MTO products energetically and efficiently. We herein constructed a stable C3 H6 -selective MOF [Mn2 (dtzip)(DMF)2 ]·3DMF·H2 O (Mn-dtzip), by the reaction between the Mn 2+ ions and 4, 6-di(1 H -tetrazol-5-yl)isophthalic acid (H4 dtzip) ligands containing carboxylic acid and tetrazole bifunctional groups. The activated material with polar honeycomb channels revealed a preferential adsorption of C3 H6 with high uptake (216.4 cm 3 g −1, 298 K and 100 kPa) and significant selectivity of C3 H6 /C2 H4 (8.6) ascribed to more accessible C3 H6 adsorption sites including exposed metal centers, uncoordinated tetrazolate N atoms, and carboxylate groups compared to C2 H4, as uncovered by theoretical simulations. Moreover, breakthrough experiments confirmed large differences in retention times between C2 H4 and C3 H6 in the separation column packed with the MOF, thus realizing an effective separation of C2 H4 –C3 H6 to not only yield ≥99.9% purity of C2 H4 by a one-step method but also greatly increased the enrichment of C3 H6, such as from 50% to 90%, in the adsorbed mixtures.